Analisis Profitabilitas Pada Bank Umum Syariah di Indonesia - Ivani Garham; Dhani Ichsanuddin Nur (I-Finance Journal, 2022)
This study was conducted to analyze and examine the effect of capital adequacy, liquidity, financing and efficiency on profitability at Islamic Commercial Banks in Indonesia from 2017-2020. A total of 14 banks as the population of this study. Samples were taken using a saturated sampling technique, namely all parts of the population as samples. The total sample was 14 Islamic commercial banks in Indonesia from 2017-2020. The method of analysis in this study is multiple regression analysis. The hypothesis was tested using the F test and the t-test. The result of this research is that capital adequacy has a significant positive effect on profitability, liquidity has a non-significant positive effect on profitability, financing has a negative and significant effect on profitability, and efficiency has an insignificant negative effect on profitability. The conclusion is the adequacy of capital and financing can contribute to the profitability of Islamic commercial banks in Indonesia. Meanwhile, liquidity and efficiency can’t contribute to the profitability of Islamic commercial banks in Indonesia.